An application of the natural area concept to East London apartment areas - Brehmer, D A E (Rhodes University, Faculty of Science, Department of Geography, 1975)
The world is faced with a population explosion, and cities are becoming ever larger. The world population will grow from its present 3500 million to more than 7 000 million by the year 2 000. The majority of cities are thus faced with the problem of housing vast numbers of people living in single family dwellings forming low density urban sprawl. Conditions are no different in South Africa where the present white population of about four million is expected to grow to between six and seven million by the year 2000. The present housing requirement (1970-75) for Whites, based on low and high population projections, is 32 732 and 40 150 houses respectively. From 1995-2000 the figures will have risen to 42 742 and 65 580 respectively. At that rate sprawl here will reach alarming proportions unless it can be curtailed by higher density housing. As the population trend does not seem likely to be reversed the problem lies in how to provide housing for an escalating population but at the same time to reduce urban sprawl and provide satisfactory living conditions.
Keywords: Natural areas -- South Africa -- East London; Apartment houses -- South Africa -- East London; Urban ecology (Sociology) -- South Africa -- East London